Pengaruh Kekerasan Verbal Terhadap Self-Esteem Remaja Akhir Di Kota Bekasi - Rizka Amalia, Ananda; Rahmat Hidayat, Dede (CV RIFAINSTITUT, 2023)
This study aims to determine the effect of verbal abuse and self-esteem on late adolescent in Bekasi. This research is a quantitative research with a Linear Regression method. The technique that used in this research is purposive sampling that has the characteristic, namely : late adolescents aged 17-22 years, domiciled in Bekasi City. The sample of this research amounted to 120 late adolescents that living in Bekasi. The data collection method in this research used an instrument of verbal abuse scale and self-esteem scale. The result of this research indicate that there is an negative effect between verbal abuse and self-esteem, with an R² value of 0.133 (p=0.01) and there was influence value of 13,3%. Based on the data analysis, it can be concluded that there is a negative effect and the opposite direction between the two variables. The more higher verbal abuse, more lowest self-esteem that would have.